Evaluation of Polysaccharide-Based Membranes for Transdermal Drug Delivery in Chronic Pain Management - Priyanshu Upadhyay (International Journal of Membranes, 2024)
In order to improve treatment effectiveness and patient compliance, chronic pain management is still a major challenge in modern healthcare, requiring creative medication delivery methods. The potential of polysaccharide-based membranes for transdermal drug delivery is assessed in this work, with particular attention to chitosan, alginate, and hydroxypropyl methylcellulose (HPMC). Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were two characterization techniques used to assess the membranes' physical and chemical properties. The kinetics of Diclofenac Sodium release was investigated in vitro. The results showed that alginate membranes produced an initial burst effect, but chitosan membranes offered a sustained release profile. Superior drug flux via alginate membranes was shown in penetration assays, suggesting that alginate membranes have a quick therapeutic effect. All membrane types were found to be safe through biocompatibility testing, with chitosan exhibiting the highest cell viability. The findings imply that polysaccharide-based membranes, in particular chitosan and alginate, are viable options for efficient transdermal drug delivery systems intended to treat chronic pain, which calls for more research into clinical applications and formulation optimisation
Keywords: Chitosan; Effectiveness of treatment; Hydropropyl methylcellulose (HPMC); Sustained Release; alginate; biocompatibility; drug release kinetics; formulation optimisation; in vitro studies; pain alleviation; pharmaceutical applications; polysaccharide membranes; transdermal drug delivery